Design and Development of Self Tuning Controller for TCSC to Damp Inter Harmonic Oscillation. (June 2017) - Kumar, M. Dilip; Sujatha, P.
Abstract: The disturbances occurring in a power system induce electromechanical oscillations of the electrical generators. These oscillations, also called power swings, must be effectively damped to maintain the system's stability. The aim is to mitigate power oscillations in power systems. There is currently interest in using Thyristor controlled series capacitors (TCSC) in transmission lines for the dual purpose of altering the steady-state power flow and enhancing system stability. Thyristor controlled series capacitors (TCSC) is one of the typical FACTS device which is used to improve the voltage profile and transient stability in power system by damping the frequency oscillation in it. This paper describes an adaptive method for control of a TCSC device for power oscillation damping. In this paper, a self-tuning PI controller for Thyristor Controlled Series Capacitor (TCSC) is proposed. Simulation results illustrate the effectiveness of the proposed self-tuning controller in simultaneously damping local-mode and inter-area oscillations. Results are compared with the fixed gain PI controller and Self-tuning PI controllers.